Comparison of inflammatory markers and microflora in cirrhotic patients with portal vein thrombosis: a retrospective study - Sun, Yanzhao; Wang, Cunkai; Wang, Dingxin; Hou, Hongtao; Zhang, Jian; Li, Yueqin; Bai, Yun (Frontiers in Medicine, 2026)
BackgroundThis study investigates inflammatory markers and blood microflora in cirrhotic patients with portal vein thrombosis (PVT).AimsThis study explores inflammatory markers and microflora in cirrhotic patients with PVT.MethodsThis retrospective study at Hebei General Hospital between September 2021 and December 2023 categorized patients into PVT and non-PVT groups. Portal and peripheral vein blood samples were collected during TIPS procedure, with inflammatory markers LPS, IL-6, IL-8, TNFα and sNox2-dp tested via ELISA and 16SrRNA sequencing of blood microflora.ResultsThe study included 28 cirrhotic patients: 12 in PVT group (5 males, mean age: 55.8 ± 11.2) and 16 in non-PVT group (13 males, mean age: 54.3 ± 13.6). Groups showed no differences in age, gender, or BMI(P > 0.05), but D-dimer levels were higher in PVT group (P < 0.05). Portal vein blood in PVT patients showed elevated LPS (34.42 vs. 13.59 pg/mL), IL-6 (38.46 vs. 18.76 pg/mL), TNFα (46.74 vs. 18.92 pg/mL), and sNox2-dp (13.03 vs. 5.13 pg/mL) vs. non-PVT patients (P < 0.05), with no peripheral blood differences.ConclusionPseudomonas and Microbacteriaceae were enriched in PVT portal blood. Rolstonia, Clostridium, Phenylobacterium, and Streptococcus correlated with LPS and IL-6 (P < 0.05), while Phenylobacterium linked to D-dimer (P < 0.05). Cirrhotic patients with PVT show higher portal vein inflammatory markers due to bacterial translocation.